Rationale, design, and methods for the Medical Optimization and Management of Pregnancies with Overt Type 2 Diabetes (MOMPOD) study - Diane C. Berry; Sonia Davis Thomas; Karen F. Dorman; Amber Rose Ivins; Maria de los Angeles Abreu; Laura Young; Kim Boggess (BMC, 2018)
Abstract Background Annually in the US, over 100,000 pregnant women with overt type 2 diabetes give birth. Strict maternal glycemic control is the key to optimizing infant outcomes. Medical treatment of type 2 diabetes in pregnancy is generally restricted to insulin, as data on the safety and efficacy of oral hypoglycemic agents in pregnancy are limited. However, over one-third of infants born to women with type 2 diabetes experience an adverse outcome, such as premature delivery, large-for-gestational age, hypoglycemia, hyperbilirubinemia, or birth trauma, suggesting that current treatment regimens fall short of optimizing outcomes. Metformin is the pharmacologic treatment of choice for type 2 diabetes outside of pregnancy. Metformin is favored over insulin because it results in less weight gain, fewer hypoglycemic episodes, and is administered orally rather than injected. However, metformin is not typically used for treatment of type 2 diabetes complicating pregnancy, mainly because no large clinical studies have been conducted to examine its use in this context. Methods/design This is a randomized double-blind multi-center clinical trial of insulin plus metformin versus insulin plus placebo for the treatment of type 2 diabetes complicating pregnancy. A total of 1200 women with type 2 diabetes will be randomized between 10 weeks 0 days' and 20 weeks 6 days' gestation and followed until 30 days after delivery. Neonate outcomes will be followed until 30 days of age. The primary aim is to compare the effect of insulin and metformin versus insulin and placebo on composite adverse neonatal outcomes, comprising perinatal mortality, preterm delivery, neonatal hypoglycemia, hyperbilirubinemia, large-for-gestational age small for gestational age, low birth weight, and/or birth trauma. Key secondary aims are to compare treatment groups for neonatal fat mass and rate of maternal hypoglycemia. Additional aims are to assess the side effects and safety of insulin and metformin among pregnant women with overt type 2 diabetes and to compare gestational weight gain among women treated with metformin plus insulin versus insulin alone. Discussion Successful completion of this study will result in high-quality, contemporary evidence for management of overt type 2 diabetes complicating pregnancy to improve neonatal outcomes. Trial registration NCT02932475 (05/17/2016).